Enhancing Student Participation in Grade V Natural and Social Science Learning through a Collaborative Approach - Sri Wahyuni (Universitas Sebelas Maret, 2022)
This research aims to enhance student participation in the learning of Natural Sciences (IPA) and Social Sciences in fifth-grade classes at Public Alementary School (SDN) 2 Banyumanis. A collaborative approach was implemented as a strategy to create a learning environment that supports active interaction among students. Through the use of teaching methods involving group discussions, collaborative projects, and problem-based activities, this research focuses on improving student engagement and developing social skills. The research method employed was classroom action research involving both teachers and fifth-grade students. The results indicated a significant improvement in student participation, both individually and in groups. Additionally, an increase in students' interest in the subjects of Natural Sciences and Social Sciences was observed.These findings underscore the importance of a collaborative approach in enhancing learning at the elementary level, particularly in the subjects of Natural Sciences and Social Sciences. The practical implications of this research provide guidance for teachers and schools in designing learning strategies that can boost student participation and enrich their learning experiences.